CANADIAN IMMIGRATION POLICY AND PRACTICE: SOME SOCIOLOGICAL IMPLICATIONS - Lawrence, Bruce Robert (My University, 2011)
In the 'Vertical Mosaic', John Porter noted that a considerable flow of post war immigrants to Canada were highly skilled and educated. During the mid-1960's the major functional requirements of the Canadian social system as it affected immigration was the requirement for increasing proportions of skilled and educated immigrants to meet the skill demands of Canada's booming economy.
As a result of this, it was hypothesized that
1. there would be an increasing proportion of immigrants intending higher occupational class levels,
2. race and ethnicity would be progressively reduced as a criterion for selecting immigrants,
3. family connection would be less of a factor in selecting immigrants intending to enter the labour force.
It was found that the basis for realizing these expected changes had been written into the Immigration Regulations; especially in the amendments to the Immigration Act of 1962 and 1967. With the introduction, in 1967, of the points system for selecting immigrants, racial and ethnic discrimination was officially eradicated as a criterion governing the admission of immigrants. Instead 'independent' applicants were to be selected on the basis of skills, education, occupational demand, area demand and some other factors. It was suggested that the two most important criteria which would ultimately determine an immigrant's admissibility were 'occupational demand' and the 'area demand' for that occupation. Also, under a separate points system 'nominated' relatives were also subject to skills and educational selection criteria as well.
The hypotheses were generally confirmed. It was found that the skill levels of immigrants in the 1960's had increased very dramatically. The proportion of immigrants who had formerly been discriminated against the most, racially and ethnically, had also increased considerably. In the case of family oriented immigration, it appeared that the proportion of nominated immigrants may have decreased considerably.
In accounting for these expected changes several factors were noted. However it must be stressed that due to the wide scope of the research that many new hypothesis were suggested and much further research proposed.
Keywords: Sociology; Sociology